Perancangan Sistem Informasi menggunakan TOGAF Dan Analisis Ward & Peppard pada SMA Santo Leo - Yefta, Vlavio Nathanael; Bernanda, Devi Yurisca (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
Santo Leo High School is a private school with high school level which is supported by the Santo Leo Foundation and is located in West Jakarta, DKI Jakarta. All current business activities have not yet maximized the full use of technology, so problems often occur such as difficulties in collecting, sorting and organizing data. The aim of this research is to help Santo Leo High School develop an information system architecture to align information technology with business needs. The data collection methods used were observation, literature study, and interviews. Development of information system architecture is assisted using TOGAF and Ward & Peppard analysis to identify needs and determine business strategies. This research produces a draft blueprint in the form of recommendations for proposed information and technology systems so that they can support the entire existing business process.